Noah's ark [videorecordings] - Hallmark Home Entertainment (New York : Hallmark Home Entertainment, 1999)
With the little help from the outside world, the brave and gentle Noah goes against all odds and builds an extraordinary ark to protect his family from the threat of great flood.
General audience.
Keywords: Bible stories $1 (BDramatic representation.s